The use of the self-management plan system of care in adult asthma - Holt, Shaun (Prim Care Respir J, 2004)
The development of self-management plans arose as clinicians tried to design better methods by which they could deliver asthma care and reduce the significant mortality and morbidity associated with this disease. The basic principles that resulted have been widely endorsed, and self-management plans are now recommended in the long-term management of adult asthma. Self-management plans essentially focus on the early recognition of unstable or deteriorating asthma, by monitoring peak flow or symptoms. Through the use of written guidelines, patients are then able to determine when it is necessary to adjust therapy or obtain medical assistance. There is now convincing evidence that the use of self-management plans by patients with asthma leads to a marked reduction in morbidity and a reduced requirement for acute medical treatment including hospital admissions. Recent research has also clarified many of the different issues concerning their structure and implementation. In some respects the skill in the use of the asthma self-management plan system of care is the ability to modify the standard plans to meet the particular needs of the individual asthmatic patient, including their preferences.